The educational value of competitive sports in developing students’ sense of national pride - Ponomarev A.V.; Obukhova O.V. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to explore the possibilities of using sports games to foster a sense of patriotism among university students. Methods and structure of the study. To assess the development of patriotic sentiments, a survey was conducted among students of Ural Federal University. The survey was administered through a questionnaire, which was completed on the Yandex form and shared via social media platforms. The survey was conducted from September to December 2024. Additionally, a content analysis was performed on the social media pages of the university’s gaming sports clubs. Results and conclusions. The findings of the online student survey indicate that game sports have the potential to foster patriotism, cultivate character traits, promote teamwork, and enhance civic engagement and national pride. The survey also explores the potential for students to engage in game sports as participants or supporters.